Judicial Reform in Latin America - (:unkn) unknown (My University, 2016)
Judicial reform has long been seen as a prerequisite for the consolidation ofdemocracy and for sustainable development in Latin America. Most countries inthe region approached the last decade of the twentieth century with weak,politically vulnerable, and ineffective judicial institutions. Few were capable ofholding executive power in proper balance, of guaranteeing the effectiveobservance of basic human and civil rights, of promoting an atmosphereconducive to economic development, especially to foreign and domesticinvestment, or of providing basic security to citizens.